Penggunaan Aplikasi Kamus Sinonim Antonim Sebagai Media Pembelajaran di MTS. Al-Hijrah NU Medan - Sri Ramadhani; Siti Rahmadhani Siregar; Saut Mardame Simamora; Jusnizar Sinaga (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Community service is an activity aimed at assisting specific communities in various activities. This activity is a part of the Tri Dharma of Higher Education, an educational activity for the community in the form of formal and non-formal education for children or students. In community service, it is expected to increase students' interest through an Indonesian language learning approach at MTS. AL-HIJRAH NU Medan, the learning approach is conducted using the play-for-study method, where Indonesian language learning will utilize a learning media in the form of a synonym and antonym dictionary application. Through the approach of learning by playing in groups, skills in understanding antonyms and synonyms are developed, so that through this game, it is hoped that students will be able to understand the similarities/differences in vocabulary. This approach provides an opportunity for students to interact with each other and express various arguments in their minds. From this activity, it is hoped that the use of the synonym and antonym dictionary application as a facility that accommodates students' learning, practicing, and playing activities through word-guessing skills can be fulfilled and beneficial to the surrounding community.